CTX-M-15-producing Klebsiella pneumoniae ST273 associated with nasal infection in a domestic cat. (March 2022) - Silva, Camila Pereira; Oliveira, Celso José Bruno de; Leite, Elma Lima; Cibulski, Samuel Paulo; Fernandes, Magda; Vasconcelos, Priscylla Carvalho; Dias, Larissa Maranhão; Silva, Núbia Michelle Vieira da; Garino Júnior, Felício; Fernandes, Artur Cesar de Carvalho
Highlights: Antibiotic-resistant infection in a cat was caused by Klebsiella pneumoniae ST273. Whole-genome sequencing revealed many genes conferring multidrug resistance. A novel putative 74 990-bp plasmid (p114PB_I) was identified, with a chimeric structure harbouring IncFIA(HI1) and IncR. A 4167-bp circular plasmid (p114PB_II) harbouring Col(pHAD28) was also identified. Potential zoonotic transmission of ESBL-producing K. pneumoniae must be considered. ABSTRACT: Objectives: The aim of this study was to investigate the genetic context of expanded-spectrum β-lactam resistance in a Klebsiella pneumoniae strain causing a hard-to-treat nasal infection in a domestic cat. Methods: A K. pneumoniae isolate was recovered from a 4-year-old male cat hospitalised in a veterinary hospital in Paraíba, Northeastern Brazil. Following phenotypic confirmation of multidrug resistance by the disk diffusion method, the genome was sequenced using an Illumina MiSeq system. Multilocus sequence typing (MLST) and structural features related to antimicrobial resistance were determined by downstream bioinformatics analyses. Results: The strain was confirmed as sequence type 273 (ST273) K. pneumoniae harbouring a variety of genes conferring antimicrobial resistance to phenicols tetracyclines, aminoglycosides, β-lactams, fosfomycin, sulfonamides and quinolones. Two plasmids were identified. Plasmid p114PB_I co-harboured a set of plasmid-borne resistance genes [ bla CTX-M−15, bla TEM−1, qnrS1, tetD, tetR, sul2, aph(6)-Id, aph(3′') and cat2 ]. Notably, the multiresistance region was characterised as a chimeric plasmid structure sharing high sequence homology with several plasmids from Enterobacteriaceae. The second plasmid (p114PB_II) was characterised as a plasmid present in many genomes belonging to K. pneumoniae. Conclusion: The genetic context of the plasmid sequences harboured by a veterinary pathogenic K. pneumoniae isolate reveals the high complexity of horizontal gene transfer mechanisms in the acquisition of antimicrobial resistance genes. The emergence, dissemination and evolution of antimicrobial resistance must be investigated from a One Health perspective.